Relentless : an immigrant story : one woman's decade-long fight to heal a family torn apart by war, lies, and tyranny - Nayzgi, Wudasie; Howe, Ken J. (Kenneth James) (Brinestone Press, 2018)
SOON AFTER RETURNING FROM EXILE to a war-torn Eritrea, a young mother receives a devastating medical diagnosis for her first-born child, and adequate treatment is unavailable inside her own country. But her desperate attempts to find help elsewhere are abruptly thwarted by a new outbreak of fighting initiated by an untested government determined to win at any cost. With her husband forced into conscription, her time and options running out, she must make a fateful decision - remain where she is and jeopardize the life of one child, or flee her beloved homeland, leaving her husband and second daughter behind... possibly forever. Relentless is the powerful and inspiring story of an Eritrean woman who faced incredible obstacles, defied a ruthless regime, and became an American immigrant success story, all while never giving up fighting for the only thing that really ever mattered: family.